A atuação do diretor de escola: entre o discurso da gestão e a prática da gerência - Sanches, Sandra Maria (2014)
The principal´s school performance is constituted of possibilities found between management discourse and management technology present in educational guidelines. Upon contradictions entailing the principal´s school performance, when it comes to the management proposal, this research has aimed in investigating how do principals in São Paulo neighborhoods seem to manifest themselves regarding their performance in demanding flux surrounding the new managerialism in cooperation with proposals coming from educational guidelines. As being a data source for research analysis, it has been used official documents such as: Educational Guidelines from the Municipal Secretariat of Education in São Paulo, during the periods from 1989 up to 2012 and, also a questionnaire with a submitted schedule to school principal´s from the municipality aiming in enabling the manifestation out around its performance. As conceptual reference regarding the study objective fundaments and data analysis it has been chosen to have the use of management and performance concepts developed by Stephen Ball and also, management concept ran by Roldão. The data analysis has pointed out to the fact that principal´s school present trends in expressing manifestations by not disagreeing in what is imposed by central and intermediate organs a behavior in which it can be justified by legal delimitation to the job position and also aiming in ensuring the expectation generated as being a performance, from the most diverse segments in a school